Faktor berisiko yang menyumbang kepada masalah residivisme : satu tinjauan sorotan literature - N.K. Tharshini,; Fauziah Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Recidivism refers to a proportion of offenders who commit repetitive offenses. In general, recidivism studies are crucial in tracking the outcomes of post-release among individuals who have committed a crime. Hence, this article is prepared to review the risk factors contributing to recidivism. All the relevant information related to recidivism was gathered from various well-established databases such as Elsevier, Sage, and Google Scholar. On the whole, the risk factors contributing to recidivism include psychopathic personality, employment opportunities, education level, history of drug abuse, duration of incarceration, acceptance of community members, and high-risk areas. As an overall impact, this review is expected to provide an in-depth understanding of the key characteristic of repeat offenders thus some effective crime prevention strategies can be developed in reducing the recidivism rate.